La mujer que convirtió a Josué en leyenda - Rubiato Díaz, Mª Teresa (Gerión. Revista de Historia Antigua, 2008)
Judith Marquet-Krause born in 1906 and deceased in 1936. Thus, 2006 is the centenary of her birth. Her short but intense career as archaeologist in the Bible Lands was of greatest importance. Her excavations at Khirbet et-Tell (1933-1935), generally identified with the Ha-‘Ay of Joshua 7-8, are pioneers in the archaeology of the country, and opened the path for its independence as a whole science. Judith Marquet-Krause expressed her well founded oppinion about the legendary character of the Joshua narratives, in a time not prone to the reception of bad news about the relations between the biblical text and the archaeological record.